2021
DOI: 10.1186/s12875-021-01369-0
|View full text |Cite
|
Sign up to set email alerts
|

Head of bed elevation to relieve gastroesophageal reflux symptoms: a systematic review

Abstract: Background Overuse of proton pump inhibitors (PPIs) – frequently used for relieving symptoms of gastroesophageal reflux disease (GORD) – raises long-term safety concerns, warranting evidence-based non-drug interventions. We conducted a systematic review to evaluate the effect of head-of-bed elevation on relieving symptoms of GORD in adults. Methods We included controlled trials comparing the effect of head-of-bed elevation interventions to control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Five systematic reviews [64][65][66][67][68] and five studies (two randomised crossover [69,70] two before-after [71,72] and one cross-sectional [46]) concluded that head-of-thebed elevation may reduce oesophageal acid exposure and reflux-like symptoms. Methods used to raise the head-ofthe-bed included wooden blocks (20 cm) [69,71], a 20 cm height/20-degree foam wedge pillow [70] and a positional device [72] (elevating the head/torso to 15 to 20 degrees together with maintaining left-side positioning).…”
Section: Lifestyle and Behaviour Advicementioning
confidence: 99%
“…Five systematic reviews [64][65][66][67][68] and five studies (two randomised crossover [69,70] two before-after [71,72] and one cross-sectional [46]) concluded that head-of-thebed elevation may reduce oesophageal acid exposure and reflux-like symptoms. Methods used to raise the head-ofthe-bed included wooden blocks (20 cm) [69,71], a 20 cm height/20-degree foam wedge pillow [70] and a positional device [72] (elevating the head/torso to 15 to 20 degrees together with maintaining left-side positioning).…”
Section: Lifestyle and Behaviour Advicementioning
confidence: 99%
“… Chandra et al (2023) proposed a hybrid model that combined CNNs and recurrent neural networks (RNNs) for more robust skin lesion classification ( Jayalakshmi & Kumar, 2019 ). Albarqouni et al (2021) presented a self-supervised learning approach that allowed models to learn from unlabeled data, resulting in enhanced generalization capabilities ( Aboubakr, Crowley & Ronfard, 2014 ). Bhattacharyya, McLean & MacIver (2021) introduced a capsule network-based architecture that captured part-whole relationships within images ( Bansal & Sridhar, 2021 ).…”
Section: Related Workmentioning
confidence: 99%
“…Although these lateral positioning studies may be helpful for older children and for the awake infant who is being fed side-lying, these positions cannot be used for sleeping because of the SIDS concerns (23). Beyond the age of 1 year when the risk of SIDS has dissipated, children with reflux symptoms frequently prefer head-of-the-bed elevation, side-lying, or prone sleeping, the latter of which has been shown to reduce reflux episodes and symptoms (24,25).…”
Section: Positioningmentioning
confidence: 99%